Mejora de la señal de ruido mediante modulación Wavelet (Revista de Investigaciones Universidad del Quindío, 2012)
In a multiuser channel (1) where signals are corrupted by Additive White Gaussian Noise (AWGN) and Multiple Access Interference (MAI), a code-division multiple access (CDMA) receiver detects the symbols, or bits, and the parameters estimates: a wavelet transform is applied to the received symbols, which have been previously coded at the transmitter by a special code; the final result is a reduction of the noise (denoi-sing), which means improvement of the performance and of the bit error rate of the system.
Keywords: Wavelets; modulation; denoising